Early-stage vaginal carcinoma – an analysis of 70 patients. Issue 2 (1st February 2004) - Otton, G. R.; Nicklin, J. L.; Dickie, G. J.; Niedetzky, P.; Tripcony, L.; Perrin, L. C.; Crandon, A. J.
Abstract : Objectives: The aims of this study were to assess outcomes and define prognostic factors for early-stage vaginal carcinoma. Methods: A retrospective analysis was performed of women with FIGO stages I and II vaginal carcinoma identified from the database of the Queensland Centre for Gynaecological Cancer between January 1982 and December 1998. Results: Seventy women were identified. The 5-year survivals for stages I and II carcinomas were 71 and 48%, respectively ( P < 0.05). Sixty-one patients (87%) had squamous cell carcinomas with a 5-year survival of 68% versus 22% for adenocarcinomas ( P < 0.01). Those women with grade 3 tumors had a 5-year survival of 40% versus 69% for grades 1 and 2 ( P < 0.05). Tumor size and site were not significant prognostic factors. Patients treated by surgery alone or with combined surgery and radiotherapy had a significantly improved survival compared to the radiation alone group ( P < 0.01). Eighty-five percent of recurrences were locoregional. The median time to relapse was 12 months after initiation of therapy. Conclusion: Tumor morphology, grade, and stage are important prognostic indicators. Measures aimed at improving local control of the disease, including surgery, are necessary.